Research on an equilibrium development model between urban and rural areas of Henan including carbon sink assets under the dual carbon goal - Xinfa, Tang; Guozu, Hao; Yonghua, Wang; Dan, Li; Yan, Luo (Frontiers in Environmental Science, 2023)
With the improvement of China’s industrialization and urbanization level, the problem of urban–rural dual structure is becoming increasingly obvious. The balanced development of urban and rural areas is a problem that China is striving to solve. Against the background of dual carbon goal, urban enterprises are reducing carbon emissions, while the rural carbon sink potential is huge, and carbon optimization is becoming the basis for balanced urban–rural development co-occurrence. This paper discusses the construction of an urban–rural mutual aid model from the perspective of carbon sink value. Using the case study method and the system theory research method, this paper analyzes the development status of rural agriculture and farmers, reveals the potential economic value of rural carbon sink assets, constructs an urban–rural mutual aid mechanism for industry feedback into agriculture, and proposes an implementation path for urban–rural mutual aid and the coordinated development of carbon sink assets under the dual carbon goal. The results show that the urban–rural mutual assistance model of carbon sink assets is conducive to the balanced development of urban and rural areas in Henan Province and the common prosperity of the people.